Elaboración de una guía de prevención y control de riesgos en proyectos de construcción en edificaciones - Flores Davila, Percy (2009)
Risky events can happen in any organization and have an adverse effect on the economic well-being in the organization. The danger can be physical, such as fire or theft, which directly affect the Organization, injury or illness of employees which results in reduction of activities, injury or damage to third parties or damage to property of others claim a compensatory payment for damages or penalty due to failure to comply with the statutory regulations. The construction industry has numerous conditions of risk. Today, with more competitive markets, introduction of new technologies and economic conditions more difficult, construction should take risks even in greater proportion, but all these risks should try to be controlled or minimized since all these risks cause a loss for the company and this is the work of a risk management.